THE SOCIALIZATION OF RIMBANG FRUIT ACTIVITY TEST RESULTS (Solanum torvum Swartz) BY HYPERSENSITIVITY METHOD SLOW TYPE - Romauli Anna Marbun; Imelda Oktaviani Br Sihombing; Kristian Cahayani Zebua (JURNAL PENGMAS KESTRA (JPK), 2022)
Immunomodulators are compounds that improve the immune system. One of the plants that has immunomodulatory activity is Rimbang Fruit (Solanum torvum swartz). The purpose of this service is to inform the immunomodulatory effect of rimbang ethanol extract in male rats which is the result of research. Research related to immunomodulatory activity was determined using a digital plethysmograph by measuring the difference between the volume of swelling of the last leg and the volume of swelling of the first leg. The treatment group was divided into 5 groups. Each group consisted of 5 CMC-Na 0.5% mice (negative control), Imboost 25 mg/kg BB (positive control), doses of EEBR100, 200 and 400 mg/kg BB and S. aureus antigens.